Dying swans and madmen: ballet, the body, and narrative cinema - McLean, Adrienne L. (Rutgers University Press, 2008)
Introduction : ballet in tin cans -- A channel for progress : theatrical dance, popular culture, and (the) American Ballet -- Gender, genre, and the ballet film through 1947 : part 1, the life of a ballerina is indeed tough -- Gender, genre, and the ballet film through 1947 : part 2, the man was mad--but a genius! -- If you can disregard the plot : the red shoes in an American context -- The second act will be quite different : cinema, culture, and ballet in the 1950s -- Turning points : -- Ballet and its bodies in the "post-studio" era
https://katalog.adlr.link/Record/0-537419942